From untried steps to omnipresence - Vesti, Peter (Torture Journal, 2022)
Contribution to the 30th Anniversary of the Torture Journal from Peter Vesti. The author presents reminds of the origin of the RCT, the first rehabilitation clinic for torture victims in Copenhagen.